Positive emotions in virtual contexts: exploring the link between leadership styles and happiness in the classroom - Cerdá Suárez, Luis Manuel (10TH International conference of educaction, reserch and innovation (ICERI2017), 2020)
In educational literature, it is important to characterize and evaluate the most influential factors in virtual learning environments. This is because the impact of these factors is relevant in order to improve the student satisfaction and happiness in the classroom. In this context, this research is aimed at understanding and describing the conditions of didactic techniques and experiences of the professor in order to improve the satisfaction and the happiness in the classroom of the students. Also, in this paper attributions consistent with the findings of Positive Psychology were analyzed and a wide spatial representation of cross-sectional nature has been conducted at universities in Mexico, Portugal and Spain between May and September 2017, within the framework of an international research of teaching innovation. In particular, this research is aimed to assess the impact of different leadership styles of the professor on happiness in the classroom, considering some personal characteristics of the students. For this reason, this study was experimental, transversal, cross-cultural, and quantitative in nature, and the sample included Business and Marketing students in those countries.
Keywords: academic engagement; beginning teachers; life satisfaction; higher-education; students; intelligence; performance; stress; diary; WOS(2)